Application of Animation Media For Introducing Diversity Culture in Students' Science Learning Class IV of SDN Pulau Dua Darat - Yudi; Amus, Sunarto; Iskandar (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
Animated media For diversity culture in learning in this modern era become the more important Because can increase enthusiasm Study student as well as provide experience learn more​ interesting and interactive because​ that , development of learning media digital based to become a need For increase quality learning . Formulation problem Research , How is the process of implementing animated media ? design made​ namely learning media Diversity Culture in learning science and science in class IV SDN Pulau Dua Darat, why animation media need to be utilized For introduce diversity culture in learning Diversity Culture in Learning students , How impact Use of Animated Media against Introducing Diversity Culture in Science Learning . Research purposes impact Use of Animated Media against introduction Introducing Diversity Culture in Science Learning . Research methods used in study This is qualitative Descriptive (qualitative descriptive research). Research results Application of animation media in science learning using animation media with allocation time in the teaching module three meetings ( 3X35 Minutes (9JP)), Appropriate learning media given to student very much influential to activity learning . If in the learning process has utilizing media, it is hoped can Motivate student in learning . Conclusion of Animation media research Need to be utilized For Introducing Diversity Culture in Learning Diversity Culture In Learning Students , At the level education basic , especially at Pulau Dua Darat Elementary School, introduction diversity culture become part important from curriculum . One of the eye relevant lessons​ For introduce values diversity This is Knowledge Natural and Social Knowledge (IPAS).